Clarithromycin versus Gemifloxacin in Quadruple Therapeutic Regimens for Helicobacter Pylori Infection Eradication - Fariborz Mansour-Ghanaei; Zahra Pedarpour; Afshin Shafaghi; Farahnaz Joukar (Middle East Journal of Digestive Diseases, 2017)
BACKGROUND Helicobacter pylori (H. pylori) infection is a major casual factor in any peptic diseases. Clarithromycin as one of the drugs recommended for the infection eradication regimen has shown different levels of resistance. The present study is comparing the effectiveness of clarithromycin- and gemifloxacin - based quadruple regimens in H. pylori eradication.